2019
DOI: 10.1016/j.colsurfa.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Improved reductive transformation of iopromide by magnetite containing reduced graphene oxide nanosacks as electron shuttles

Abstract: The novel application of magnetite containing reduced graphene oxide nanosacks (MrGO-N) as electron shuttles to improve the reductive degradation of pharmaceutical pollutant, iopromide (IOP), was evaluated. The MrGO-N were synthesized by ultrasonicated nebulization process, and their physicochemical characterization was performed by potentiometric titrations, zeta potential, high resolution transmission electron microscopy (HR-TEM), X-ray diffraction, as well as by Raman and Fourier transform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It also could be feasible that the graphitic network within the carbon-based materials promoted enhanced electron transfer as suggested previously. 28,29 The present study also revealed that engineered conductive materials, such as those synthesized here by cold oxygen plasma, could be applied in WWTP to prevent N 2 O emissions, which are very common in full-scale denitrifying processes. 11 Certainly, application of oxidized carbonaceous material to sludge incubations greatly enhanced the N 2 O reduction rate, which otherwise was marginal in the absence of this conductive material (Table 4; Fig.…”
Section: Discussionmentioning
confidence: 54%
“…It also could be feasible that the graphitic network within the carbon-based materials promoted enhanced electron transfer as suggested previously. 28,29 The present study also revealed that engineered conductive materials, such as those synthesized here by cold oxygen plasma, could be applied in WWTP to prevent N 2 O emissions, which are very common in full-scale denitrifying processes. 11 Certainly, application of oxidized carbonaceous material to sludge incubations greatly enhanced the N 2 O reduction rate, which otherwise was marginal in the absence of this conductive material (Table 4; Fig.…”
Section: Discussionmentioning
confidence: 54%